Consumer Willingness to Pay a Premium for Sustainable products utilizing recycled plastics in Hungary - Influence of Environmental Awareness and Branding Strategy - Sarközi, David; Szabo, Zoltan (Journal of Entrepreneurship, Business and Economics; Vol 13 No 2 (2025), 2025)
This study investigates Hungarian consumers’ willingness to pay a premium for sustainable products made from recycled plastics, with a focus on the role of environmental awareness and branding strategies. Following a literature review, premium pricing was examined in relation to consumer value perception and eco-consciousness. The primary research was based on a quantitative online survey conducted among Hungarian residents. Descriptive and inferential analyses were used to explore the connections between environmental attitudes, branding strategies, willingness to pay a premium, and demographic variables. The results show that factor price is remaining very important in Hungary, further on product durability and certifications related to CO2 neutrality significantly enhance consumers’ willingness to pay more. Well-educated, higher-income respondents from the capital city placed greater emphasis on green products and were more likely to accept higher prices than others. Contrary to expectations, influencer marketing and brand trust had a weaker impact. The findings offer practical recommendations for companies aiming to strengthen eco-branding and pricing strategies in Hungary’s sustainability market. Research Paper Keywords: Consumer Behavior, Willingness to Pay, Sustainable Products, Recycled Plastics, Branding Strategies Reference to this paper should be made as follows: Sarközi, D., & Szabo, Z. (2025). Consumer Willingness to Pay a Premium for Sustainable products utilizing recycled plastics in Hungary - Influence of Environmental Awareness and Branding Strategy. Journal of Entrepreneurship, Business and Economics , 13 (2), 84–117.